Disarming Staphylococcus aureus from destroying human cells by simultaneously neutralizing six cytotoxins with two human monoclonal antibodies. Issue 1 (1st January 2018) - Rouha, Harald; Weber, Susanne; Janesch, Philipp; Maierhofer, Barbara; Gross, Karin; Dolezilkova, Ivana; Mirkina, Irina; Visram, Zehra C.; Malafa, Stefan; Stulik, Lukas; Badarau, Adriana; Nagy, Eszter
ABSTRACT: Pathogenesis of Staphylococcus aureus is increasingly recognized to be driven by powerful toxins. Staphylococcus aureus employs up to six pore-forming toxins to subvert the human host defense and to promote bacterial invasion: alpha-hemolysin that disrupts epithelial and endothelial barriers and five leukocidins that lyse phagocytes involved in bacterial clearance. Previously, we described two human monoclonal antibodies (mAbs), ASN-1 that neutralizes alpha-hemolysin and four leukocidins (LukSF-PV, LukED, HlgAB, HlgCB), and ASN-2 that inactivates the 5 th leukocidin, LukGH. In this study we tested the individual and combined effects of ASN-1 and ASN-2 in multiple in vitro models employing relevant human target cells. We found that diverse S. aureus isolates with different genetic backgrounds (based on MLST- and spa -typing) and antibiotic sensitivity (both MRSA and MSSA) displayed greatly different cytotoxin expression patterns influenced by the type of growth medium used. Both mAbs were required to fully prevent the lysis of human neutrophils exposed to the mixture of recombinant cytotoxins or native toxins present in the culture supernatants of S.   aureus isolates. Flow cytometry confirmed the protective effects of ASN-1 + ASN-2 (known as ASN100) on granulocytes, monocytes, NK-cells and T-lymphocytes. ASN-1 alone preserved the integrity of a 3D-primary culture of human tracheal/bronchial mucociliary epithelial tissue infected with S. aureus . We conclude that simultaneous inhibition of alpha-hemolysin and five leukocidins by ASN100 blocks cytolytic activity of S. aureus towards human target cells in vitro .